Urgency of Establishing a National Spices and Herbal Agency In Realizing Golden Indonesia 2045 - Muhammad Haris Zulkarnain; Yaya Sunaryo; Yudi Pratama; Riskal Arief; Asy’ari Muchtar; Irma Suryani Harahap (International Journal of Science and Environment (IJSE), 2025)
Indonesia has a very large potential for "spices and herbs." Both are abundant as one of the natural resources bestowed by God Almighty. These resources have strategic value in the fields of health, medicine, industry, beauty and economy. However, their utilization has not been optimal in supporting sustainable national economic growth. Therefore, a national agency is needed that specifically manages spices and herbs to increase competitiveness, added value, and their contribution to the Indonesian economy. This study aims to analyze the urgency of establishing the National Spice and Herbal Agency in order to support the vision of Indonesia Emas 2045. The method used is descriptive qualitative research with a case study approach, using secondary data from various relevant sources. The results of the study show that although Indonesia has abundant spice and herbal resources, their management is still sectoral and not yet integrated. Therefore, the establishment of a national agency that specifically handles this sector is a strategic step to create more effective, sustainable governance, and is able to increase the contribution of the spice and herbal sector to the national economy, including in Non-Tax State Revenue (PNBP) and exports.